2021
DOI: 10.1016/j.jinf.2020.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholinesterase associated with COVID-19 pneumonia severity and mortality

Abstract: Serum cholinesterase associated with COVID-19 pneumonia severity and mortality Dear Editor, Kunutsor and Laukkanen have written to this journal regarding elevated admission levels of markers of liver injury (alanine aminotransferase and aspartate aminotransferase, gammaglutamyltransferase, alkaline phosphatase and total bilirubin) may be associated with progression to severe disease or death in COVID-19. 1 On the other hand, serum cholinesterase plays an important role in the inflammatory response and may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 9 publications
6
34
0
Order By: Relevance
“…Moreover, we found in the current study that SChE activity lower than 5,000 UI/L was associated with a poor outcome in multivariate analysis. Our results confirm the results of a recent study performed by Nakajima et al [ 31 ] who found that cholinesterase level on admission was an independent predictor of the severity of COVID-19 pneumonia and mortality. In fact, cholinesterase activity is thought to be affected by acute-phase infections and inflammatory processes [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found in the current study that SChE activity lower than 5,000 UI/L was associated with a poor outcome in multivariate analysis. Our results confirm the results of a recent study performed by Nakajima et al [ 31 ] who found that cholinesterase level on admission was an independent predictor of the severity of COVID-19 pneumonia and mortality. In fact, cholinesterase activity is thought to be affected by acute-phase infections and inflammatory processes [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Studies have found that they are able to modulate the activity of several receptors, including ion channels, nicotinic acetylcholine receptors (nAChRs) and acetylcholine-degrading enzymes (acetylcholinesterases), thus resulting in the alteration of acetylcholine levels and of cholinergic transmission [22][23][24] . Regarding cholinesterases, a potential association between cholinesterase levels and severity of pneumonia in COVID-19 patients has been proposed 25 .…”
Section: Conotoxinsmentioning
confidence: 99%
“…Studies have found that they are able to modulate the activity of several receptors, including ion channels, nicotinic acetylcholine receptors (nAChRs) and acetylcholine-degrading enzymes (acetylcholinesterases), thus resulting in the alteration of acetylcholine levels and of cholinergic transmission 25 27 . Regarding cholinesterases, a potential association between cholinesterase levels and severity of pneumonia in COVID-19 patients has been proposed 28 .…”
Section: Resultsmentioning
confidence: 99%